Estrogen to Progesterone Ratio and Fluid Regulatory Responses to Varying Degrees and Methods of Dehydration - Giersch, Gabrielle E. W.; Charkoudian, Nisha; Morrissey, Margaret C.; Butler, Cody R.; Colburn, Abigail T.; Caldwell, Aaron R.; Kavouras, Stavros A.; Casa, Douglas J. (Frontiers in Sports and Active Living, 2021)
The purpose of this study was to investigate the relationship between volume regulatory biomarkers and the estrogen to progesterone ratio (E:P) prior to and following varying methods and degrees of dehydration. Ten women (20±1 y, 56.98±7.25 kg, 164±6 cm, 39.59±2.96 mL•kg•min-1) completed four intermittent exercise trials (1.5 h, 33.81.3ºC, 49.54.3% relative humidity). Testing took place in two hydration conditions, dehydrated via 24-hour fluid restriction (Dehy, USG>1.020) and euhydrated (Euhy, USG≤1.020), and in two phases of the menstrual cycle, the late follicular phase (days 10-13) and midluteal phase (days 18-22). Change in body mass (%BMΔ), serum copeptin concentration, and plasma osmolality (Posm) were assessed before and after both dehydration stimuli (24-hour fluid restriction and exercise heat stress). Serum estrogen and progesterone were analyzed pre-exercise only. Estrogen concentration did not differ between phases or hydration conditions. Progesterone was significantly elevated in luteal compared to follicular in both hydration conditions (Dehy – follicular: 1.156±0.31, luteal: 5.190±1.56 ng•mL-1, P<0.05; Euhy – follicular: 0.915±0.18, luteal: 4.498±1.38 ngmL-1, P<0.05). As expected, E:P was significantly greater in the follicular phase compared to luteal in both hydration conditions (Dehy – F:138.94±89.59, L: 64.22±84.55, P<0.01; Euhy – F:158.13±70.15, L: 50.98±39.69, P<0.01). Copeptin concentration was increased following 24-hour fluid restriction and exercise heat stress (mean change: 18±9.4, P<0.01). We observed a possible relationship of lower E:P and higher copeptin concentration following 24-hour fluid restriction (r=-0.35, P=0.054). While these results did not reach the level of statistical significance, these data suggest that the differing E:P ratio may alter fluid volume regulation during low levels of dehydration but have no apparent impact following dehydrating exercise in the heat.